2005
DOI: 10.1021/jm049375b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cellular Studies of Nonaggregated Water-Soluble Phthalocyanines

Abstract: Water-soluble phthalocyanines are promising photosensitizers for application in cancer therapy and in the photoinactivation of viruses. The water-soluble zinc(II) phthalocyanines 5 and 6 were synthesized by converting the corresponding ester derivative 4 into the sodium carboxylate and carboxylic acid species. Compound 5 can be solubilized in water as a monomeric species, as demonstrated by UV/vis and fluorescence spectroscopy. These compounds were characterized by analytical and spectroscopic methods and, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(66 citation statements)
references
References 58 publications
5
57
0
2
Order By: Relevance
“…On the other hand, it is also possible that the localization of Si(sol) 2 Pc in lipid droplets is not the prime reason for its high phototoxicity, because redistribution of this compound over the cytosol was observed upon illumination (Figure 5c). Similar behavior has been found by Liu et al 51 who observed that PSs, that is, ZnPc derivatives containing carboxylate groups accumulated in lysosomes and redistributed upon brief light exposure. Redistribution of Si(sol) 2 Pc may be due to the destruction of the lipid droplets by ROS.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, it is also possible that the localization of Si(sol) 2 Pc in lipid droplets is not the prime reason for its high phototoxicity, because redistribution of this compound over the cytosol was observed upon illumination (Figure 5c). Similar behavior has been found by Liu et al 51 who observed that PSs, that is, ZnPc derivatives containing carboxylate groups accumulated in lysosomes and redistributed upon brief light exposure. Redistribution of Si(sol) 2 Pc may be due to the destruction of the lipid droplets by ROS.…”
Section: Discussionsupporting
confidence: 87%
“…Compared to the traditional synthetic route using 4-nitrophthalonitrile, a higher yield was obtained by the substitution reaction of the hydroxyl compound with 4-chlorophthalonitrile. Substitution reactions are a common synthetic route for the water-soluble zinc phthalocyanines [38]. In our prior study, water-soluble glucose conjugated zinc phthalocyanines were prepared in high yield by this route [32].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the inclusion of the NLS signal in the peptide did not direct the ZnPc into the nucleus, as observed also for other PSs studied by the same group. However it was hypothesized a possible release of the conjugates from the lysosomes during irradiation and subsequent relocalization in cellular sites more sensitive to light induced oxidative stress like the nucleus [83][84][85].…”
Section: Photosensitizers Conjugated To Peptidesmentioning
confidence: 99%